Transcatheter pulmonary valve perforation using chronic total occlusion wire in pulmonary atresia with intact ventricular septum - Shweta Bakhru; Shilpa Marathe; Manish Saxena; Sudeep Verma; Rajan Saileela; Tapan K Dash; Nageswara Rao Koneti (Wolters Kluwer Medknow Publications, 2017)
Background: Perforation of pulmonary valve using radiofrequency ablation in pulmonary atresia with intact ventricular septum (PA IVS) is a treatment of choice. However, significant cost of the equipment limits its utility, especially in the developing economies. Objective: To assess the feasibility, safety, and efficacy of perforation of pulmonary valve using chronic total occlusion (CTO) wires in patients with PA IVS as an alternative to radiofrequency ablation. Methods: This is a single.center, nonrandomized, retrospective study conducted during June 2008 to September 2015. Twenty-four patients with PA IVS were selected for the procedure during the study period. The median age and weight of the study population were 8. days and 2.65 kg, respectively. Four patients were excluded after right ventricular angiogram as they showed right ventricular-dependent coronary circulation. The pulmonary valve perforation was attempted using various types of CTO wires based on the tip load with variable penetrating characteristics. Results: The procedure was successful in 16 of twenty patients using CTO wires: Shinobi in nine, Miracle in four, CROSS-IT in two, and Conquest Pro in one. Two patients had perforation of right ventricular outflow tract (RVOT). Pericardiocentesis was required in one patient to relieve cardiac tamponade. Later, the same patient underwent successful hybrid pulmonary valvotomy. The other patient underwent ductus arteriosus. (DA) stenting. Balloon atrial septostomy was needed in three cases with systemic venous congestion. Desaturation was persistent in five cases necessitating DA or RVOT stenting to augment pulmonary blood flow. There were two early and two late deaths. The mean follow-up was 22.66. ± 16 months. Three patients underwent one and half ventricle repair and one Blalock-Taussig shunt during follow-up. Conclusion: Perforation of the pulmonary valve can be done successfully using CTO wires in selected cases of pulmonary atresia with intact ventricular septum.